1963
DOI: 10.1073/pnas.49.6.892
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Valine and Isoleucine in the Presence of a Particulate Cell Fraction of Neurospora

Abstract: It has been established that valine is synthesized from pyruvate in a series of at least four steps, and that isoleucine is synthesized in a series of four similar steps from pyruvate and a-ketobutyrate. The four enzymes involved are apparently common to both pathways, but this has not been definitely proved in any one case. The enzymes will be described here as the condensing enzyme, which produces aacetolactate and a-acetohydroxybutyrate from pyruvate, and pyruvate + aketobutyrate, respectively; the reductoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1967
1967
1974
1974

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…The antipolar effect of the E-amber mutation on DH is also consistent with this theory. It is noteworthy that certain enzymes of the isoleucine-valine biosynthetic pathway appear to be aggregated in N. crassa (34); nevertheless, we have been unable to demonstrate such aggregation in extracts of our wild-type E. coli strain. The three enzymes diffuse independently of each other, and TD and DH separate readily during ammonium sulfate fractionation.…”
Section: Discussioncontrasting
confidence: 55%
“…The antipolar effect of the E-amber mutation on DH is also consistent with this theory. It is noteworthy that certain enzymes of the isoleucine-valine biosynthetic pathway appear to be aggregated in N. crassa (34); nevertheless, we have been unable to demonstrate such aggregation in extracts of our wild-type E. coli strain. The three enzymes diffuse independently of each other, and TD and DH separate readily during ammonium sulfate fractionation.…”
Section: Discussioncontrasting
confidence: 55%
“…Wild type mycelium of known age was harvested after 35 hr of growth from a minimal agar plate overlaid with dialysis membrane and was then fixed for electron microscopy. Seven samples were harvested at the same time from regions of a single mycelial pad known to be 4, 8,12,16,20,24, and 30 hr old.…”
Section: Resultsmentioning
confidence: 99%
“…The a-ketobutyrate inhibition of purified AAS was not unexpected. Wagner and co-workers (27) have shown that a-ketobutyrate will competitively inhibit valine synthesis from pyruvate as determined by in situ assay of the Cmp from Neurospora. The competitive inhibition of purified mitochondrial AAS is presumably due to the ability of a-ketobutyrate to occupy the active site(s) as a pyruvate analogue.…”
Section: Discussionmentioning
confidence: 99%